«Auf Wiedersehen in Florenz!» Voci di ebrei tedeschi dall'Italia - Rocchi, Federica (Biblioteca di Studi di Filologia Moderna, 2022)
«Auf Wiedersehen in Florenz!» Voci di ebrei tedeschi dall'Italia presents a new Italian perspective on German exile literature, which is related to the migration of German-Jewish intellectuals to Florence after 1933. A reconstruction of the historical context is provided by shedding light on the intersections between Italian, German and Jewish cultures in the Florentine context but also on the literary production of the involved authors. Migration writers such as Alice Berend, Rudolf Borchardt, Karl Wolfskehl and Walter Hasenclever are presented in relation to the process of writing in exile, whereas the works of Max Krell, Monika Mann, Otti Binswanger-Lilienthal and Georg Strauss are analyzed in the section devoted to post-exile.